Barnardo's misleading survey: publicity at what cost?. (30th November 2011) - McCartney, Margaret
Abstract : A survey by the charity purporting to show anti-child sentiment in the UK got a great deal of publicity. However, Margaret McCartney says that the exercise was a lesson in how to ask leading questions